2014
DOI: 10.1371/journal.pgen.1004139
|View full text |Cite
|
Sign up to set email alerts
|

Large Inverted Duplications in the Human Genome Form via a Fold-Back Mechanism

Abstract: Inverted duplications are a common type of copy number variation (CNV) in germline and somatic genomes. Large duplications that include many genes can lead to both neurodevelopmental phenotypes in children and gene amplifications in tumors. There are several models for inverted duplication formation, most of which include a dicentric chromosome intermediate followed by breakage-fusion-bridge (BFB) cycles, but the mechanisms that give rise to the inverted dicentric chromosome in most inverted duplications remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 68 publications
8
66
0
5
Order By: Relevance
“…In this regard, it will be interesting to evaluate if particular patterns of mitochondrial genomic instability are observed in the context of these disorders. Genomic rearrangements associated with inversions in the human nuclear genome have also been linked to leukemia, autism, and intellectual disability (Pui et al 1992;Hermetz et al 2014). It would therefore also be interesting to determine whether such rearrangements also occur through a U-turn-like mechanism and lead to the onset of such phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it will be interesting to evaluate if particular patterns of mitochondrial genomic instability are observed in the context of these disorders. Genomic rearrangements associated with inversions in the human nuclear genome have also been linked to leukemia, autism, and intellectual disability (Pui et al 1992;Hermetz et al 2014). It would therefore also be interesting to determine whether such rearrangements also occur through a U-turn-like mechanism and lead to the onset of such phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This type of rearrangement forms via a distinct mechanism involving a dicentric chromosome intermediate that breaks to give rise to a characteristic terminal deletion adjacent to inverted duplications separated by a short disomic spacer. 33 Another duplication that appeared to be terminal by microarray analysis turned out to be in direct orientation. WGS of EGL825's terminal duplication suggested an interchromosomal duplication between chromosomes 9 and 12 (Table S2); however, FISH confirmed that this is an intrachromosomal duplication of the short arm of chromosome 9.…”
Section: Complex Duplicationsmentioning
confidence: 99%
“…Inverted duplications adjacent to terminal deletions have a characteristic appearance via microarray analysis and in almost all cases occur de novo. 33,63 Terminal gains are most often unbalanced translocations, but in rare cases might be inverted or direct intrachromosomal duplications. Chromosomes with a terminal duplication of one end and a terminal deletion of the other end can be generated by recombination within an inversion loop.…”
Section: Duplications With Common Breakpointsmentioning
confidence: 99%
“…The main mechanism for inverted duplication formation was originally believed to be a double strand break leading to telomere loss and fusion of sister chromatids (U-type exchange) followed by breakage of the dicentric chromosome and breakage-fusion-bridge cycles [Knijnenburg et al, 2007]. Recently, a fold-back mechanism has been described whereby after the initial double strand break and telomere loss single-stranded DNA folds back and intra-strand pairs resulting in an intrachromosomal inverted duplication [Hermetz et al, 2014]. This same mechanism has been put forward to explain the formation of inverted duplication on acentric markers [Murmann et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…A clear distinction can be made between these two mechanisms through the identification of a single copy region between the deleted and duplicated regions in case of NAHR based rearrangement. Through the use of next generation sequencing, Hermetz et al [2014] proposed a new mechanism of formation based on an intrastrand fold-back of a broken DNA that anneals to itself at site of inverted sequence homology, which may represent the leading pathway to generation of the dicentric.…”
Section: Introductionmentioning
confidence: 99%